Functional characterization of DEEPGENES to enhance deeper rooting in cereal crops - Fusi, Riccardo (2022)
Global food security and climate change represent major challenges faced by humankind during this century. Developing deeper rooting, more resource efficient crops represents an attractive solution to increase crop production sustainably whilst also enhancing soil carbon (C) sequestration. For example, planting maize varieties with a root system 0.5m deeper than currently sown in USA is predicted to improve foraging for water and nitrogen resources in sub-soil layers whilst burying up to two thirds of carbon related to US transportation emissions. The aim of this PhD project is to identify and characterise key genes that control anatomical and architectural traits contributing to deeper rooting in cereal crops such as maize and barley (as part of the DEEPER project funded by the ARPA-E ROOTS initiative).